Umiejętności menedżerskie i struktura czasu pracy kadry kierowniczej w jednostkach służby zdrowia - Paszkowski, Jerzy (Managerial Skills and Work Time Structure of the Mangers in Heath Care Units., 2006)
The author analyzes results of examination which refer to management's work time structure and managerial skills in health care units. Among all managerial functions such as planning, organizing, recruiting, firing, motivating, controlling and current directing, the most time consuming for managers is just the last one - current directing. But the more time managers devote on current directing, the more indifferently organization is managed. As far as technical, motivating and communicating skills are concerned, almost in all cases there should be bigger than managers have in reality. The results proofed that managers have a critical approach to their own skills and think that they should have a knowledge in all ranges of management activity. An insufficient education level and preparation to managing are mainsprings of such estate, so constant trainings of managers in health care units are necessary. The actions which refer to mission, vision, strategy forming and controlling, which inclusive wider functional fields in organization, are necessary. One single person do not have the ability to posses all skills and knowledge in all compound areas so new workers recruiting is necessary. In conclusion the recruiting function has a strategic meaning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 101-110